Analisis Pengaruh Ketanggapan Karyawan, Empati Karyawan Dan Kehandalan Karyawan Terhadap Kualitas Pelayanan Serta Dampaknya Terhadap Kepercayaan Konsumen (Studi Pada Guest House Griya Bougenville Semarang) - Harimurti, Krisna; Sugiarto, Sugiarto (Diponegoro Journal of Management, 2013)
This study aims to determine how much influence of employee responsiveness, employeeempathy, and employee reliability to service quality. Service quality can influence to consumer trust. The population used in this study is the guest in Griya Bougenville who ever live in there or more than once times.Samples in this study were 100 respondents and the techniques used are non-probability sampling technique with Accidental Sampling approach. The researcher use validity test, reliabilitytest, linier regression analysis, and hypothesis test supported by SPSS computer program version17. Independent variables are employee responsiveness, employee emphaty, and employee reliability. Intervening variable is service quality, and dependent variable is consumer trust.The  result  of  research  showed  that  employee  responsiveness,  employee  empathy,  andemployee reliability  have positive and significant impact on service quality. Service quality have positive and significant impact to Consumer Trust.